Commentary: Time for a paradigm shift in conceptualizing risk factors in sports injury research - Cameron, K. L. (Journal of Athletic Training, 2010)
Aktueller Blick auf die Bestimmung von Risikofaktoren in der Forschung zum Thema Sportverletzungen.